Irish University Press series of British parliamentary papers : Third and fourth reports from the select committee on East India with appendices : Vol- 2 : colonies East India - Great Britain. Parliament. House of Commons (Shannon : Irish University Press, 1970)
This set consolidates all papers relating to penal colonies covering the period 1810-1869. Australian content is prevalent through all 16 volumes.
From the collection of Angus Downie, a well respected political journalist for The Examiner in Launceston, Tasmania and noted disability campaigner.
Keywords: Penal colonies -- Great Britain -- History -- Sources